THE LINK BETWEEN TECTONIC AND PALEOCLIMATIC EVENTS AT 2.8-2.5 MA BP IN THE LAKE BAIKAL REGION - Prokopenko A.A.; Karabanov E.B.; Williams D.F.; Kuzmin M.I.; Gvozdkov A.A.; Khursevich G.K. (My University, 2001)
The records of diatom abundance, clay fraction content and magnetic susceptibility from Lake Baikal drill core BDP-96-1 reflect the climate-driven Plio-Pleistocene evolution of the Lake Baikal sedimentation system. In addition to the dramatic variations in the proxy records in response to the Northern Hemisphere ice ages, the Baikal record also indicates climatic deterioration from 2.8 to 2.5MaBP with evidence for an early Siberian glaciation around the Matuyama/Gauss paleomagnetic reversal boundary. The drill core data also allow correlation of this early glacial interval with the basin-wide seismic sequence boundary B10, which marks the unconformity produced by the active neotectonic phase in the Baikal rift zone. At the BDP-96 drill site, however, the strong B10 acoustic reflection was produced not by an erosional boundary, but instead by deposition of glacial clay layers.The paleomagnetic age scale of BDP-96-1 constrains the upper age of the Neobaikalian uplift/subsidence phase in the Baikal-Sayan region at ca. 2.5MaBP. The coincident timing of the paleoclimatic and tectonic events recorded in Lake Baikal sediments suggests a close causal link between regional tectonics and climate and indicate that the late Pliocene uplift contributed to the initiation of the early glaciation in southeast Siberia between 2.8 and 2.6MaBP by creating an elevated terrain with lower snowline, favorable for alpine glaciation, and by changing the heat balance of the region.
Keywords: Baikal; Pleistocene; Pliocene; Tectonics and climate; Cenozoic::Quaternary::Pleistocene; Cenozoic::Neogene::Pliocene; Кайнозой::Четвертичная::Плейстоцен; Кайнозой::Неоген::Плиоцен